2009
DOI: 10.1126/scisignal.261pe12
|View full text |Cite
|
Sign up to set email alerts
|

When the Endogenous Hallucinogenic Trace Amine N,N -Dimethyltryptamine Meets the Sigma-1 Receptor

Abstract: N,N-dimethyltryptamine (DMT) is a hallucinogen found endogenously in human brain that is commonly recognized to target the 5-hydroxytryptamine 2A receptor or the trace amine–associated receptor to exert its psychedelic effect. DMT has been recently shown to bind sigma-1 receptors, which are ligand-regulated molecular chaperones whose function includes inhibiting various voltage-sensitive ion channels. Thus, it is possible that the psychedelic action of DMT might be mediated in part through sigma-1 receptors. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 42 publications
2
101
0
3
Order By: Relevance
“…The activity of σ 1 receptors could be reciprocally inhibited by an association with binding immunoglobulin protein (BiP) through the formation of a σ 1 receptor -BiP complex, and σ 1 -receptor agonists could exert a chaperone activity with respect to σ 1 receptors by breaking the tether of the σ 1 receptor -BiP complex (18). Recently, the endogenous hallucinogenic amine N,N-dimethyltryptamine (DMT) was shown to be an endogenous σ-receptor ligand, and DMT as well as σ 1 -receptor agonists were shown to induce the dissociation of σ 1 receptors from the σ 1 receptor -BiP complex (22). Taken together, these results suggest that κ-opioid receptor agonists and non-competitive NMDA-receptor antagonists may regulate endogenous σ 1 -receptor systems by regulating DMT, which induces a hallucinogenic effect.…”
Section: Hallucination and σ 1 Receptorsmentioning
confidence: 99%
“…The activity of σ 1 receptors could be reciprocally inhibited by an association with binding immunoglobulin protein (BiP) through the formation of a σ 1 receptor -BiP complex, and σ 1 -receptor agonists could exert a chaperone activity with respect to σ 1 receptors by breaking the tether of the σ 1 receptor -BiP complex (18). Recently, the endogenous hallucinogenic amine N,N-dimethyltryptamine (DMT) was shown to be an endogenous σ-receptor ligand, and DMT as well as σ 1 -receptor agonists were shown to induce the dissociation of σ 1 receptors from the σ 1 receptor -BiP complex (22). Taken together, these results suggest that κ-opioid receptor agonists and non-competitive NMDA-receptor antagonists may regulate endogenous σ 1 -receptor systems by regulating DMT, which induces a hallucinogenic effect.…”
Section: Hallucination and σ 1 Receptorsmentioning
confidence: 99%
“…Recently, biochemical, physiologic, and behavioral experiments demonstrated that DMT is an endogenous agonist at s-1 receptors (s-1Rs) (12); the hypothetical signaling scheme triggered by this binding has also been reported (13). These facts, together with our intention to provide insight into this issue, led us to develop in vivo DMT (compared with tryptamine) studies in animal models.…”
mentioning
confidence: 95%
“…-1 Receptor ligands, including neurosteroids, regulate this receptor-chaperone activity in an agonist/antagonist fashion Hayashi et al, 2009). In addition, -1 receptors were recently found to bind the psychedelic drug N,N-dimethyltryptamine and eventually produce a blockade of sodium channels, possibly through translocation of -1 receptors from the ER to the plasma membrane region (Fontanilla et al, 2009;Johannessen et al, 2009;Su et al, 2009).…”
mentioning
confidence: 99%